A Tunable High-Sensitivity Refractive Index of Analyte Biosensor Based on Metal-Nanoscale Covered Photonic Crystal Fiber With Surface Plasmon Resonance - Zhenkai Fan (IEEE Photonics Journal, 2019)
A tunable high-sensitivity gold-film covered photonic crystal fiber refractive index biosensor based on surface plasmon resonance is proposed. The finite element method is used to analyze and discuss the sensing performance of the biosensor to the analyte. The radio interference (RI) of the analyte is detected by flowing it though the outer fiber surface. The phase matching condition is satisfied between the fundamental mode and the surface plasmon polariton modes, whose resonance coupling can be achieved. The complete coupling and incomplete coupling are excited as the analyte RI increases, and the resonance strength of the complete coupling is stronger than that of the incomplete coupling. It can be proved by calculation that the resonance coupling for the fundamental mode and the fifth-, sixth-, or seventh-order SPP mode has been obtained at different wavelengths. However, the biosensor has obtained four ranges including the analyte RI from 1.33 to 1.38, 1.405 to 1.425, 1.425 to 1.445, and 1.405 to 1.445, respectively. Their average sensitivities are 1971, 8220, 15180, and 5140 nm/RIU, and the linearities are 0.82982, 0.99771, 0.98104, and 0.99837, respectively. In short, the superior performance of tunable, wide-range, and high sensitivity is obtained, which shows a bright application prospect in the field of bio-detection technology.